(untitled) (Journal of the College of Basic Education, 2022)
The tagged research (violence and tenderness and their impact on the form and content of artistic work) represents a modest scientific effort in order to determine the artist’s stylistic projection of violence and tenderness on the forms of his artwork, as well as revealing the impact of psychological and intellectual stressors - implicitly - on the aesthetic of visual artwork. The matter that prompted the researcher to collect scientific materials to serve the title of this study, in terms of three chapters ... The first chapter included the research methodology that includes (the problem of the research, its importance, objectives, limitations and determining the most important terms). As for the second chapter, it was devoted to the theoretical framework in which the researcher dealt with major topics summarized as follows: First / Violence and its psychological and artistic consequences / It touched upon the psychological - dark factors - stressing the artist’s psyche, which determines his behavior and his outlook on life and through his artistic works. Second / Raqqa and its psychological and technical consequences: Here it was touched that the human life was established on the basis of a delicate and sensitive equation between the elements of "reason" and "emotion" and that any defect in this equation causes a state of turmoil and dispersion, and then pressure factors are established on it by the artist and who During which for his artwork. Third / Artistic works and pressing factors: As there is no doubt that for every artwork there are external factors that press on it and that will control the process of its artistic and expressive production. Among these influences are: 1 -Psychological and intellectual pressure / each artist has intellectual and psychological references that are responsible for defining his behaviors in society, and they themselves constitute effective pressure factors affecting the production of his artwork. 2- Physical and physical reasons / which constitutes a direct pressure factor on the artwork by restricting them to the use of raw materials. 3- Lack of culture / There is no doubt that the artist - as well as the recipient - who does not have enough culture to present his artistic productions, his artistic works will not be at the level that we aspire artistically and culturally, which constitutes a negative pressure factor on the entire artistic process. 4- Poverty in power / where there is no doubt that the poor physical condition of the artist and the economic level of the society in which he lives revolves, a major cause for pressing his artworks to rise to the required artistic and cultural leel. 5- The authority of the state, society, or belief / It is certain that the reasons for shackling the artist’s imaginations and preventing the emergence of free expressive ideas to society by the dominant authority or custom, traditions or religious beliefs, are very significant psychological and intellectual pressure factors on the artist and the recipient on the one hand. As for the third chapter, the researcher assigned it to the research procedures included (research community, samples, methodology, and tool, and then intentionally analyzing the samples chosen by the researcher) ..